Pengaruh Profitabilitas, Ukuran Perusahaan, dan Umur Perusahaan Terhadap Ketepatan Pelaporan Keuangan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2018-2021 - Eka Novia; Anik Malikah; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research was conducted at a manufacturing company with the method used in the research is a quantitative method using logistic regression analysis test, regression model feasibility test, overall regression model test, coefficient of determination and wald test. The purpose of this study was to analyze the effect of profitability, company size, and company age on the accuracy of financial reporting. The dependent variable is the accuracy of financial reporting. by using a purposive sampling sample of 66 manufacturing companies. Processed using SPSS with the results of research on profitability does not affect the accuracy of financial reporting with a significant value of 0.260 greater than 0.05, company size has a significant and positive effect on the accuracy of financial reporting with a significant value of 0.004 less than 0.05, age the company has a significant and positive effect on the accuracy of financial reporting with a significant value of 0.028 less than 0.05.Keywords : Profitability, company size, company age, accuracy of financial reporting.